2008
DOI: 10.1186/bcr2208
|View full text |Cite|
|
Sign up to set email alerts
|

Buthionine sulfoximine sensitizes antihormone-resistant human breast cancer cells to estrogen-induced apoptosis

Abstract: Introduction Estrogen deprivation using aromatase inhibitors is one of the standard treatments for postmenopausal women with estrogen receptor (ER)-positive breast cancer. However, one of the consequences of prolonged estrogen suppression is acquired drug resistance. Our group is interested in studying antihormone resistance and has previously reported the development of an estrogen deprived human breast cancer cell line, MCF-7:5C, which undergoes apoptosis in the presence of estradiol. In contrast, another es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 42 publications
11
58
0
Order By: Relevance
“…Before gene expression microarray studies were carried out, the estrogen-dependent WS8 (29-31), ED-resistant but apoptosis-refractory 2A (25,30,31), and apoptosis-sensitive 5C cells (24,29,32) were characterized to confirm previously reported growth responses, biomarker status, and estrogen response element (ERE) -regulated transcriptional activity (SI Results and Discussion, SI Methods, and Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before gene expression microarray studies were carried out, the estrogen-dependent WS8 (29-31), ED-resistant but apoptosis-refractory 2A (25,30,31), and apoptosis-sensitive 5C cells (24,29,32) were characterized to confirm previously reported growth responses, biomarker status, and estrogen response element (ERE) -regulated transcriptional activity (SI Results and Discussion, SI Methods, and Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…When cells were grown under long-term estrogendeprived conditions (>1 y), cells lost their dependency on estrogen for proliferation but maintained expression of ER. Subsequent studies of E 2 action on the growth of long-term estrogen-deprived MCF-7 cells in vitro at high (23) and low concentrations in vitro and in vivo (24,25) indicated that the concept of "an estrogen purge" (19) to destroy antihormone-resistant cells could be applied to the treatment of breast cancer. This concept has now been translated to clinical trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in GSH homeostasis have been implicated in the etiology and progression of some diseases and breast cancer (Townsend et al 2003) and studies have shown that elevated levels of GSH prevent apoptotic cell death whereas depletion of GSH facilitates apoptosis (Anderson et al 1999). Our laboratory has found evidence which suggests that GSH participates in retarding apoptosis in antihormoneresistant MCF-7:2A human breast cancer cells, which have ~60% elevated levels of GSH compared to wild-type MCF-7 cells and unable to undergo estrogen-induced apoptosis within 1 week unlike MCF-7:5C cells, and that depletion of GSH by 100 µM of L-buthionine sulfoximine (BSO), a potent inhibitor of glutathione biosynthesis, sensitizes these resistant cells to estradiol-induced apoptosis (Lewis-Wambi et al 2008). However, the question arises as to the actual mechanism of the apoptotic trigger mediated by the ER complex.…”
Section: Mechanism Of Estrogen-induced Apoptosismentioning
confidence: 99%
“…It has been reported that oestrogen protects pancreatic beta [11] , retina ganglion [12] , neuronal [13] , bone [14] , and heart [15] cells via inhibition of apoptosis. However, oestrogen also plays a role in increasing apoptosis in other cell types, such as osteoclasts [16] , breast cancer cells [17] , and leukaemia cells [18] . For human hearing, oestrogen seems to have protective effects [19] .…”
Section: Introductionmentioning
confidence: 99%